2022
DOI: 10.1002/cpe.6851
|View full text |Cite
|
Sign up to set email alerts
|

Content‐based image retrieval for super‐resolutioned images using feature fusion: Deep learning and hand crafted

Abstract: An innovative image retrieval agenda by concatenating deep learning features from GoogleNet and low‐level features from HSI and RGB color space is proposed in this article. Most of the CNN features suffer from loss of information due to image resize as a pre‐processing stage. To reduce this information loss super‐resolution technic is used for resizing images. An improved form of dot‐diffused block truncation coding is used for extracting RGB handcraft features. To discover the interdependencies between color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Pradhan, J., et al [7] proposed a regions-of-attention-based feature fusion technique for image retrieval, here authors used multi-directional texture features with spatial correlation-based color features to derive the image semantics. Pathak, D., et al [9] The CRMLBP is computed for the sign-difference, magnitudedifference, and central gray value patterns in the RGB color space and their histograms are concatenated. The feature weights are optimized using Particle Swam Optimization (PSO) technique.…”
Section: IImentioning
confidence: 99%
See 3 more Smart Citations
“…Pradhan, J., et al [7] proposed a regions-of-attention-based feature fusion technique for image retrieval, here authors used multi-directional texture features with spatial correlation-based color features to derive the image semantics. Pathak, D., et al [9] The CRMLBP is computed for the sign-difference, magnitudedifference, and central gray value patterns in the RGB color space and their histograms are concatenated. The feature weights are optimized using Particle Swam Optimization (PSO) technique.…”
Section: IImentioning
confidence: 99%
“…The efficiency of the CBIR system greatly depends upon the visual feature selection. The high-level semantic features [3,7] of an image are its color, shape, structure, Zernike values, and histogram are used for manual image annotation and are less biased with noise [8,9]. Features represented using the spatial layout of the pixels within an image patch are referred as low-level features or local descriptors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, their method's performance is sensitive to weight selection. Pathak and Raju [17] fused multiple image features, both non-deep-learning features and deep learning features, and showed that more features in fusion lead to improved performance. However, as with [16], their performance is also sensitive to weight selection.…”
Section: B Deep Feature Similaritymentioning
confidence: 99%